Symptoms during initiation of a ketogenic diet: a scoping review of occurrence rates, mechanisms and relief strategies - Skartun, Oddbjørn; Smith, Callum Rhys; Laupsa-Borge, Johnny; Dankel, Simon Nitter (Frontiers in Nutrition, 2025)
BackgroundEvidence for the clinical utility of ketogenic diets (KD) is mounting. The transition to a KD (keto-induction) can however trigger unpleasant transient symptoms (≪keto-flu≫) which may deter continued adherence. Knowledge of strategies that mitigate symptoms during keto-induction may facilitate adoption of a KD.AimWe aimed to perform a scoping review of the available scientific literature with regards to symptom occurrence rates, possible mechanisms and proposed interventions for symptom relief during keto-induction.MethodsEmbase, Medline and Web of Science electronic databases were searched systematically using terms associated with the KD and keto-induction in conjunction with terms capturing adverse effects. In addition, additional relevant studies were retrieved from the identified articles' references.ResultsThe available literature on keto-induction symptoms is highly heterogenous, but common transient symptoms are reported across multiple populations, including descriptions of “keto-flu,” nausea, emesis, reduced appetite, hypoglycaemia, acidosis, increased risk of kidney stones, altered liver biochemistry, and skin rash. Mechanisms have been proposed based on general insights into physiology, but few have been empirically tested. However, approaches to reduce symptoms of keto-initiation are reported, including avoidance of the traditionally used fasted initiation and supplementation of medium-chain triglycerides (MCT) and ketone salts. There is a physiological rationale for supplementation with electrolytes and ketone esters, but a lack of clinical studies documenting their effect.ConclusionSeveral transient symptoms have been associated with keto-induction, although a limited number of studies have directly examined them, or the mechanisms and possible interventions for symptom alleviation. Further research is warranted to close knowledge gaps highlighted in this review.